UNCTAD mandates on commodities : 2008-2016 : the road from Accra to Doha (UN New YorkUS, 2013)
Reproduces the texts of the Accra Accord and Doha Mandate relating specifically to commodities as well as texts of a more general nature - including on institutional issues - that are relevant to carrying out the mandate on commodities.
Keywords: COMMODITIES